The virR/virS locus regulates the transcription of genes encoding extracellular toxin production in Clostridium perfringens. - Ba-Thein, W (1996)
Extracellular toxin production in Clostridium perfringens is positively regulated by the two-component regulatory genes virR and virS. Northern (RNA) blots carried out with RNA preparations from the wild-type strain 13 and the isogenic virR and virS mutants TS133 and JIR4000 showed that the virR and virS genes composed an operon and were transcribed as a single 2.1-kb mRNA molecule. Primer extension analysis led to the identification of two promoters upstream of virR. Hybridization analysis of the mutants and their complemented derivatives showed that the virR/virS system positively regulated the production of alpha-toxin (or phospholipase C, theta-toxin (perfringolysin O), and kappa-toxin (collagenase) at the transcriptional level. However, the modes of regulation of these genes were shown to differ. The theta-toxin structural gene, pfoA, had both a major and a very minor promoter, with the major promoter being virR/virS dependent. The colA gene, which encodes the kappa-toxin, had two major promoters, only one of which was virR/virS-dependent. In contrast, the alpha-toxin structural gene, p1c, had only one promoter, which was shown to be partially regulated by the virR and virS genes. Comparative analysis of the virR/virS-dependent promoters did not reveal any common sequence motifs that could represent VirR-binding sites. It was concluded that either the virR/virS system modulates its effects via secondary regulatory genes that are specific for each toxin structural gene or the VirR protein does not have a single consensus binding sequence.